Agents of the Internet apocalypse - Gladstone, Wayne (Gladstone, Wayne. Internet apocalypse trilogy, 2015)
"Gladstone, the so-called 'Internet Messiah, ' has not only failed to bring back the Web, but his search has landed him in a New York City psychiatric ward. The rest of the world isn't doing so well either, filled with disconnected Internet users still jonesing for a fix, and an increasingly draconian government, interrogating and detaining anyone deemed a 'person of interest' under the NET Recovery Act. For Gladstone, however, finding the Net is less important than heading to Los Angeles to win back his ex-wife"--